Some properties for exact generalized processes - Simsen, Jacson; Capelato, Érika [UNESP] (Springer Nature, 2015)
In this work, we define an exact generalized process and we establish some results such as monotonicity, compactness, and upper semicontinuity for the multivalued process defined by the exact generalized process. The main result is on compactness, invariance, and attraction properties of ω-limit sets.
Keywords: Generalized processes; Multivalued processes; Nonautonomous dynamical systems; Pullback attraction